A systems approach to modeling the water-energy-land-food nexus : system dynamics modeling and dynamic scenario planning. - Amadei, Bernard, 1954- (Momentum Press sustainable structural systems collection., 2019)
Water, energy, land, and food (WELF) resources are critical components in the overall discourse on sustainable human development. Over the next 50 years, rapid population, urbanization, and economic growth worldwide will create unprecedented demands for such resources, as well as for health, transportation, waste disposal, communication, and other services. The discussion on how to meet human needs for water, energy, land, and food and how to guarantee their respective securities has changed over time. The traditional way has been to look at all four sectors in isolation, regardless of whether one is interested in supply and demand, infrastructure planning and design, resource management and allocation, and/or governance. Since 2011, however, there has been a new emphasis on understanding the interdependency of the four sectors through the so-called WELF nexus. The approach presented in this book responds to the overall agreement in the WELF nexus literature that the management and allocation of water, energy, land, and food resources at the community level need to be examined in a more systemic, multidisciplinary, participatory, and practical manner while seeking to increase synergies and reduce trade-offs. Such an integrated approach is not yet mainstream among those involved in the science and policy decision aspects of the nexus. This book was written to explore the value proposition of that approach. This two-volume book describes a flexible and adaptive system-based methodology and associated guidelines for the management and allocation of community-based WELF resources. Volume 1 reviews the existing literature about the nexus and focuses on defining the landscape in which it operates. The proposed methodology is also outlined. Volume 2 explores the quantitative and qualitative modeling of the nexus and landscape using system modeling tools including system dynamics. It presents a road map for the formulation, simulation, selection, and ranking of possible interventions, as well as the development of possible intervention plans.